A Comparison of the Sensory Profile and Sensory Processing Measure Home Form for Children with Fetal Alcohol Spectrum Disorders. (1st November 2013) - Hansen, Kathleen Deirdre; Jirikowic, Tracy
ABSTRACT This exploratory study compared the performance of children with fetal alcohol spectrum disorders (FASD; n = 11) and children with typical development (TD) without alcohol exposure (n = 12) on the Short Sensory Profile (SSP) and Sensory Processing Measure (SPM) Home Form. The child's primary caregiver completed both measures. For children with FASD, 90.9% had probable or definite differences on the SSP and 81.8% had some problems or definite dysfunction on the SPM Home Form. All children with TD (100%) scored in the typical range on total scores for both measures. For the children with FASD, the percent agreement between the two measures was 36.6% for the three classification categories (typical, probable/some, and definite) and 81.8% when classification was collapsed into two categories (typical and probable/definite difference). Both measures detected sensory processing differences for children with FASD, however, categorization of clinical severity varied based on the cutoffs used.